Enhancing Staff’s Work Motivation in Vietnamese Companies - Rewel Jiminez Santural Jose, Ho Thien Thong Minh, Syed Ehsan Ullah, Muhammad Sadiq, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, with the trend of globalization, with increasingly fierce competition, it is required that businesses that want to succeed must constantly improve their quality and improve themselves to be able to stand firm in the market. In addition, people are being considered as an invaluable asset, which is a fundamental factor that determines the existence and development of an enterprise. In the context that society is gradually shifting to a knowledge-based economy, a business, even with rich and strong financial resources, becomes meaningless without the human element. Without effective employees, the organization cannot achieve its goals. When employees are motivated to work, they will work very enthusiastically, passionately and that will create high labor productivity, contributing to the achievement of business and production goals of the enterprise. This article analyzes in-depth the specific work motivation of staff in several Vietnamese enterprises.